Model dekonstruksi bangunan berkelanjutan berbasis â€œreverse 4D BIMâ€ - Tri Joko Wahyu Adi; Novalia Andriyani (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2023)
Indonesia's increasing population and limited land have made the need for shelter, workplaces, and vertical buildings increase. As a consequence, buildings that have exceeded their service life, have changed their function, have been damaged by a disaster, and are not fit for function need to be demolished. Demolition needs special attention because the process requires complex planning, is hidden, carries high risks, and generates more than 40% of the total solid waste in developing countries. In Indonesia in particular, deconstruction has not been carried out by many demolition service providers. The government does not yet have comprehensive regulations for sustainable building demolition. This study aims to propose a sustainable demolition model by prioritizing the conservation of demolition waste material. In this study, the